Gestão Documental no âmbito energias renováveis: Estudo de caso da empresa Gonçalves Rapazote, Lda. - Tiago Miguel Araújo Pereira (2021)
Document management is an area that is in constant development and has registered a heightened concern by all entities, be they public or private, to proceed towards a proper information management and in this way facilitate the services administered daily by all collaborators. As such, this thesis was created in the corporate scope, most notably in the company Gonçalves Rapazote Lda, included amongst the department of production of wind power and consequently the area of renewable energies, to demonstrate that Document Management is a field that encompasses any existing sector. This project aims to carry out an evaluation of the current situation of said business followed by the implementation of a document management strategy previously defined. This way, the strategy established had as a main foundation the model MOREQ 2010 with the purpose of trying to bring closer the existing resources in the organization with a system of document management, strengthening their use. To accomplish these foreseen results, it was indispensable to create a map of the processes involved, through the BPMN language, elaboration of a filing plan, to guarantee the organization of the documents according to the context of their creation, moreover the adoption of a selection table to establish the deadlines of administrative conservation of the documents and their destination at the end of the established deadline. All steps previously described had an important part towards the implementation of the document management module, included in the company ERP, for it to be possible to successfully optimize the document management practices by digital means in the company Gonçalves Rapazote which has been specified as the main objective to accomplish in this project. Once all tests of usability performed to the new module are concluded and the employee satisfaction has been surveyed, towards the new process of document management, it has been verified that the intended results were achieved with success.